Midwives’ views and experiences on birthing positions utilised during labour in maternity units: A scoping review of qualitative studies. - Mokgabodi LDM; Ngema; Masubelele (Student's Journal of Health Research Africa, 2026)
Introduction: Childbirth remains a personal experience for mothers giving birth globally. Maternal positions during childbirth significantly affect the birthing process and its outcomes. Midwives play a crucial role in facilitating these positions, directly supporting Sustainable Development Goal 3 by reducing maternal and neonatal mortality. Their expertise ensures safe, evidence-based care, promoting health and well-being for mothers and infants throughout the birthing process. Aim: To map the evidence from the published literature on midwives' views and experiences of birthing positions used during labour in maternity obstetric units. Methods: A comprehensive literature search was conducted across multiple search databases, including Scopus, Medline, PubMed, ProQuest, Springer, and Wiley. A scoping review was conducted in line with the steps of Arksey and O’Malley. Results: The search yielded 248 studies; six were selected for the final evaluation. The chosen review articles were all published between 2015 and 2025. Six qualitative studies were included in the final review. The thematic analysis identified seven key themes: 1) midwives' views and beliefs about birthing positions, 2) institutional and organisational obstacles, 3) power relations and professional hierarchies, 4) cultural competence and woman-centred care, 5) maternal autonomy and informed choice, 6) enablers of physiological birth, and 7) safety concerns and risk assessment. Conclusion: This review highlights the need to integrate midwives’ insights into practice to enhance maternal and neonatal outcomes and improve the overall childbirth experience.